1997
DOI: 10.1055/s-2007-978997
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy of Physiological Responses to Hypoglycemia: Relevance to Clinical Hypoglycemia in Type I (Insulin Dependent) Diabetes Mellitus*

Abstract: Hypoglycemia elicits a characteristic sequence of responses in healthy humans. These responses (and their arterialized venous glycemic thresholds) include: 1) Decreased insulin secretion (approximately 4.5 mmol/L). 2) Increased glucose counterregulatory hormone (glucagon, epinephrine, growth hormone and cortisol) secretion (approximately 3.6-3.8 mmol/L). 3) Symptoms of hypoglycemia (approximately 3.0 mmol/L). 4) Cognitive dysfunction (approximately 2.6 mmol/L). Thus, insulin secretion decreases as plasma gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
48
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 15 publications
4
48
1
Order By: Relevance
“…However, during hypoglycaemia counterregulatory mechanisms will override the glucagon suppression [41]. In our study, the hypoglycaemic threshold of about 4 mmol/l that has been established for counterregulation [42] was only reached in one animal, while the average values, though below basal, remained above the threshold. However, it has been reported that a non-hyperinsulinaemic-induced decrease in glucose of 0.6 mmol/l to 5.2 mmol/l can result in a fall of plasma insulin and an increase in glucagon, indicating that in the dog the pancreatic alpha cell is very sensitive to a drop in glucose [43].…”
Section: Discussioncontrasting
confidence: 41%
“…However, during hypoglycaemia counterregulatory mechanisms will override the glucagon suppression [41]. In our study, the hypoglycaemic threshold of about 4 mmol/l that has been established for counterregulation [42] was only reached in one animal, while the average values, though below basal, remained above the threshold. However, it has been reported that a non-hyperinsulinaemic-induced decrease in glucose of 0.6 mmol/l to 5.2 mmol/l can result in a fall of plasma insulin and an increase in glucagon, indicating that in the dog the pancreatic alpha cell is very sensitive to a drop in glucose [43].…”
Section: Discussioncontrasting
confidence: 41%
“…They described a significant correlation with the value of glucose nadir and the response of cortisol and growth hormone. Cryer et al (18) proved in several studies investigating diabetic patients that the absolute value of glucose nadir determines the extent of counterregulatory responses. The studies of Landon et al and Cryer et al support our hypothesis, that the duration of hypoglycemia in the insulin tolerance test can be shortened by early glucose intervention without affecting the response of cortisol and growth hormone if the glucose nadir is maintained.…”
Section: Discussionmentioning
confidence: 99%
“…Our proposal is quite consistent with this hypothesis, since hypoglycemia is a classic inducer of the stress response. Thus, for example, reduction of blood glucose stimulates secretion of glucocorticoids (a classic stress response) in mice [126], rats [127] and humans [128]. Similarly, reduction of blood glucose activates the sympathetic nervous system, also a classic stress response, in mice [129], rats [127] and humans [128].…”
Section: Contextmentioning
confidence: 99%
“…Thus, for example, reduction of blood glucose stimulates secretion of glucocorticoids (a classic stress response) in mice [126], rats [127] and humans [128]. Similarly, reduction of blood glucose activates the sympathetic nervous system, also a classic stress response, in mice [129], rats [127] and humans [128]. Indeed, hypoglycemia even produces homotypic densitization, a classic feature of stress responses, in mice [129], rats [127] and humans [130].…”
Section: Contextmentioning
confidence: 99%